2021
DOI: 10.1186/s12902-021-00782-x
|View full text |Cite
|
Sign up to set email alerts
|

DPARD: rationale, design and initial results from the Dutch national diabetes registry

Abstract: Background Treatment of diabetes mellitus has majorly improved over the past century, however, the disease burden is high and its prevalence still expanding. Further insight in the diabetes population is imperative to improve the quality of diabetes care by enhancement of knowledge-based diabetes management strategies. To this end, in 2017 a Dutch nationwide consortium of diabetologists, paediatric endocrinologists, and diabetes patients has founded a national outpatient diabetes care registry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It is unlikely that diminished data quality would explain the lower performance of BMI, since data quality in DPARD improves every time data is provided by a hospital and our study includes only hospitals delivering data in both 2019 and 2020. [15] Furthermore, the fact that blood pressure was recorded more frequently in 2020 in patients visiting the outpatient clinic in either 2019 or 2020 seems discordant with a decline in outpatient visits. Yet in patients visiting in both years, blood pressure performance was decreased in 2020, suggesting an increase in data quality over time as a likely explanation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that diminished data quality would explain the lower performance of BMI, since data quality in DPARD improves every time data is provided by a hospital and our study includes only hospitals delivering data in both 2019 and 2020. [15] Furthermore, the fact that blood pressure was recorded more frequently in 2020 in patients visiting the outpatient clinic in either 2019 or 2020 seems discordant with a decline in outpatient visits. Yet in patients visiting in both years, blood pressure performance was decreased in 2020, suggesting an increase in data quality over time as a likely explanation.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale and design of the DPARD registry has been described in detail previously. [15] In short, DPARD is a nationwide quality registry of adult and pediatric diabetes patients treated in all secondary and tertiary outpatient care across the Netherlands. Five hospitals provided data in 2019 and 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The Dutch Pediatric and Adult Registry of Diabetes (DPARD) is a national quality registry of adult and pediatric patients with diabetes mellitus treated in secondary and tertiary outpatient care across the Netherlands [ 12 ]. The registry was launched in 2017 by the BIDON foundation, a Dutch nationwide consortium of diabetologists, pediatric endocrinologists, and diabetes patients.…”
Section: Methodsmentioning
confidence: 99%
“…10 Future studies should further delve into these differences in the use of hospital care and how they are associated with clinical outcomes of patients with diabetes across SES categories, for example, with data from the Dutch Paediatric and Adult Registry of Diabetes (DPARD). 33 It is known from observational studies that SES influences clinical outcomes such as glycaemic control in type 1 diabetes. 10,30 In addition, a recent study has shown that CSII and rtCGM, mediate the association between SES and glycaemic control.…”
Section: Sexmentioning
confidence: 99%